River flow conditions and dynamic state analysis of Pahang river - Muhammad Barzani, Gasim (2013)
Pahang River (Sg. Pahang) is the longest river in Peninsular Malaysia. Flood is a common event in Pahang River Basin during wet season which triggered by monsoon season. The hydrodynamic study of Pahang River should be well understood especially when it is a target of northeast monsoon which influenced the Pahang River Basin every year (from November to March). 17 river cross section stations were selected and used to measure its drainage capacity, hydraulic parameters and estimation of flow discharge. Long term (1980 to 2009) variation of hydrologic data series comprised of river flow, river stage and rainfall data were analyzed based on the Department of Irrigation and Drainage (DID) Malaysia record. Monthly rainfall was recorded from Sg. Yap, Temeiloh and Lubuk Paku Rainfall Stations. Two hydrologic sampling trips had been carried out; first sampling on January 2010 and second sampling on February 2010. The study indicates that velocity and river flow measurement during first sampling ranged from 0.308 to 0.582 m sec-1 and 153.282 to 439.684 m3 sec-1. Meanwhile, during second sampling, the velocity and river flow ranged from 0.217 to 0.484 and 52.071 to 304.485 m3 sec-1, respectively. Floods were occurred annually at Pahang River especially during northeast monsoon these events are expected to be stimulated by the inconsistent condition of width and depth along Pahang River which finally create sedimentation and meandering characteristic. ©2013 Science Publication.